A liposomal carbohydrate vaccine, adjuvanted with an NKT cell agonist, induces rapid and enhanced immune responses and antibody class switching - Ji-Xiang Jia; Sen-Lin Peng; Ndayambaje Yvan Kalisa; Qiang Chao; Zhifang Zhou; Xiao-Dong Gao; Ning Wang (Journal of Nanobiotechnology, 2023)
Abstract Background Congenital disorders of glycosylation (CDGs) are genetic diseases caused by gene defects in glycan biosynthesis pathways, and there is an increasing number of patients diagnosed with CDGs. Because CDGs show many different clinical symptoms, their accurate clinical diagnosis is challenging. Recently, we have shown that liposome nanoparticles bearing the ALG1-CDG and PMM2-CDG biomarkers (a tetrasaccharide: Neu5Ac-α2,6-Gal-β1,4-GlcNAc-β1,4-GlcNAc) stimulate a moderate immune response, while the generated antibodies show relatively weak affinity maturation. Thus, mature antibodies with class switching to IgG are desired to develop high-affinity antibodies that may be applied in medical applications. Results In the present study, a liposome-based vaccine platform carrying a chemoenzymatic synthesized phytanyl-linked tetrasaccharide biomarker was optimized. The liposome nanoparticles were constructed by dioleoylphosphatidylcholine (DOPC) to improve the stability and immunogenicity of the vaccine, and adjuvanted with the NKT cell agonist PBS57 to generate high level of IgG antibodies. The results indicated that the reformulated liposomal vaccine stimulated a stronger immune response, and PBS57 successfully induce an antibody class switch to IgG. Further analyses of IgG antibodies elicited by liposome vaccines suggested their specific binding to tetrasaccharide biomarkers, which were mainly IgG2b isotypes. Conclusions Immunization with a liposome vaccine carrying a carbohydrate antigen and PBS57 stimulates high titers of CDG biomarker-specific IgG antibodies, thereby showing great potential as a platform to develop rapid diagnostic methods for ALG1-CDG and PMM2-CDG. Graphical Abstract